Impact of MBG on Student Nutrition and Physical Activity in Palembang - M. Armando Yusaromi; Hartati; Reza Resah Pratama (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
Developing high quality human resources is the key to the success of national development. Efforts to improve the quality of human resources can be achieved through the educational process. A factor contributing to educational success is the nutritional adequacy of school children, which plays a role in increasing their cognitive capacity, stamina, and learning endurance. In Indonesia, many nutritional problems are still found that negatively impact children's concentration, academic achievement, and physical fitness. As an intervention to address this issue, the government launched the Free Nutritious Meal Program (MBG) in schools. This study used a cross-sectional design. The research population consisted of students from SMPN 35 Palembang. Sampling was conducted using a purposive sampling technique with a total of 84 participants. Data analysis was performed using the chi-square test. The results showed that 66.7% of students who did not routinely receive the MBG program had abnormal nutritional status, and 58.3% of students who did not routinely receive MBG had low physical activity. It was concluded that there is a significant relationship between the provision of MBG and nutritional status (p=0.011) and physical activity (p=0.008). It is recommended to continuously monitor and evaluate the long-term implementation of the MBG program, which can provide a positive influence on health and education in Indonesia.